Application of the Glasgow coma scale: a bibliometric analysis of publications in the field of Nursing - Sousa, Luana Miranda de (2021)
The article aims to carry out a bibliometric analysis of different studies on the Application of the Glasgow Coma Scale, in order to raise a better understanding of the theme of this study. For this, a bibliometric study was carried out based on bibliographic research on the thematic Glasgow Coma Scale and application of the Glasgow Coma Scale. Nine articles were selected, from the seventeen found, based on the analysis of these articles it was possible to identify and achieve its main objective, which was to carry out a bibliometric analysis of different studies on the Application of the Glasgow Coma Scale, where it can be identified that this it is widely used today to identify neurological disorders, monitor the evolution of the level of consciousness, predict prognoses and standardize language among health professionals. Furthermore, from the selection of 9 articles, it was found that 78% of the scored studies achieved positive objectives, demonstrating the knowledge of professionals and the advantages of applying ECG. On the other hand, 11.11% of the results were unsatisfactory and/or intermediate, that is, a sum of 22, 22% of the scored articles had negative results, which leads to the understanding that, in some application, knowledge of ECG is unsatisfactory.